Design of an automated drip irrigation system. A case study in a blueberry cultivation nursery (LACCEI, 2024)
This research was carried out with the aim of designing an automated system based on Arduino UNO for drip irrigation of blueberry cultivation. In the current context, maintain an irrigation system that optimizes water consumption while leading to efficient crop development, represents a problem that leads us to use innovations to automate an irrigation system and create an ideal condi-tion for crops. In this regard, a methodology was developed based on the analysis of components suitable for the needs of the project, subsequently the system proposed in the Proteus software and the programming that couples the parameters of the tem-perature and humidity conditions using the Arduino IDE environment was designed Overall, all the work made possible the 3D construction in the Sketchup software with the characteristics of the design proposed in a nursery located in Cajamarca-Peru. Therefore, the results obtained show that the irrigation system is responsible for supplying the water efficiently, in which the water pump operates when the temperature level is high, and the humidity level is below the established conditions.